Controllable Cell Deformation Using Acoustic Streaming for Membrane Permeability Modulation. Issue 3 (21st December 2020) - Guo, Xinyi; Sun, Mengjie; Yang, Yang; Xu, Huihui; Liu, Ji; He, Shan; Wang, Yanyan; Xu, Linyan; Pang, Wei; Duan, Xuexin
Abstract: Hydrodynamic force loading platforms for controllable cell mechanical deformation play an essential role in modern cell technologies. Current systems require assistance from specific microstructures thus limiting the controllability and flexibility in cell shape modulation, and studies on real‐time 3D cell morphology analysis are still absent. This article presents a novel platform based on acoustic streaming generated from a gigahertz device for cell shape control and real‐time cell deformation analysis. Details in cell deformation and the restoration process are thoroughly studied on the platform, and cell behavior control at the microscale is successfully achieved by tuning the treating time, intensity, and wave form of the streaming. The application of this platform in cell membrane permeability modulation and analysis is also exploited. Based on the membrane reorganization during cell deformation, the effects of deformation extent and deformation patterns on membrane permeability to micro‐ and macromolecules are revealed. This technology has shown its unique superiorities in cell mechanical manipulation such as high flexibility, high accuracy, and pure fluid force operation, indicating its promising prospect as a reliable tool for cell property study and drug therapy development. Abstract : This article presents a novel hydrodynamic force loading platform based on acoustic streaming generated from a gigahertz ultrasonic device for controllable cell deformation and real‐time 3D cell shape analysis. The platform is applied for cell membrane permeability modulation, and a novel phenomenon that fast and periodic cell deformation will facilitate the intracellular transportation of large cargos is observed.